Bovine Tooth Discoloration Induced by Endodontic Filling Materials for Primary Teeth - Samantha Rodrigues Xavier; Katerine Jahnecke Pilownic; Andressa Heberle Gastmann; Mariana Silveira Echeverria; Ana Regina Romano; Fernanda Geraldo Pappen (International Journal of Dentistry)
Objective. This study evaluated the discoloration potential of endodontic materials used in primary teeth. Material and Methods. Dentine-enamel blocks were prepared from 75 bovine teeth, assorted in five experimental groups (n=15). The tested materials included an MTA-based material; zinc oxide and eugenol cement (ZOE); Vitapex; and calcium hydroxide thickened with zinc oxide (Calen + ZO). The color measurements were performed using a spectrophotometer at the following intervals: prior to (T0) and after placement of the filling (T1) and after 1 week (T2), 1 month (T3), 3 months (T4), 6 months (T5), and 9 months (T6). Data were submitted to ANOVA with repeated measures and Tukey’s test. Results. The time had a significant effect on the color variation (ΔE00⁎) (p<0.0001). The effect of the materials on the color variation (ΔE00⁎) was statistically significant (p=0.004). Interactions between time and materials demonstrated a significant effect on the values (ΔE00⁎) (p<0.0001). The ZOE cement showed the highest darkening effect (p=0.018). Conclusion. The MTA-based material showed the smallest discoloration during the experimental time; however, it was similar to the other materials and to the control group. Zinc oxide and eugenol showed higher discoloration.